Permutability of Backlund transformation for N=1 supersymmetric sinh-Gordon - Gomes, J. F. [UNESP]; Ymai, L. H. [UNESP]; Zimerman, Abraham Hirsz [UNESP] (Elsevier B.V., 2009)
The permutability of two Backlund transformations is employed to construct a nonlinear superposition formula to generate a class of solutions for the N = 1 super sinh-Gordon model. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Backlund transformation; Supersymmetric sinh-Gordon; Non-linear superposition formula